India’s civil nuclear cooperation strategy: comparing approaches of Manmohan Singh and Narendra Modi’s cabinets - K. A. Ananina (Сравнительная политика)
The article compares the approaches undertaken by the government of former Indian prime-minister Manmohan Singh and that of Narendra Modi to promoting international cooperation in civil nuclear energy following the U.S.-India nuclear deal. The fi ndings indicate that Modi’s nuclear policy complements and, paradoxically, advances key initiatives of the opposing United Progressive Alliance. Specifi cally, Modi’s nuclear policy aims to foster solid ties with major global suppliers of uranium and atomic production while creating favourable external and internal environment conducive to India’s accessing international nuclear market where Indian companies would compete as suppliers of indigenous low and medium power reactors, varied nuclear equipment and materials as well as relevant services, for instance, on design, construction and commissioning of power plants.